Clinical ethics committees and the formulation of health care policy. (1st April 2001) - Doyal, Len
Abstract : For some time, clinical ethics committees (CECs) have been a prominent feature of hospitals in North America. Such committees are less common in the United Kingdom and Europe. Focusing on the UK, this paper evaluates why CECs have taken so long to evolve and assesses the roles that they should play in health care policy and clinical decision making. Substantive and procedural moral issues in medicine are differentiated, the former concerning ethicolegal principles and their paradigmatic application to clinical practice and the latter dealing with how such application should be negotiated in the face of disagreement and/or uncertainty. It will be argued that the role of CECs is both substantive and procedural. Provided that they do not overstep their appropriate moral and professional boundaries, CECs will be shown to have an important and positive function in improving hospital care within the UK and elsewhere.